2014
DOI: 10.1159/000358560
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Circulating Testosterone Levels Determined by LC-MS/MS and by a Commercially Available Radioimmunoassay in Healthy Girls and Boys during the Pubertal Transition

Abstract: Background: Accurate and selective assessment of testosterone requires use of a sensitive LC-MS/MS method, especially at low levels as those seen in young children. Methods: The present longitudinal study of 20 healthy children from the Copenhagen Puberty Study followed every 6 months for 5 years evaluates the longitudinal increase in serum testosterone before, during and after pubertal onset quantified by a newly developed LC-MS/MS method in comparison with immunoassay. Testosterone concentrations in serum sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 18 publications
(20 reference statements)
2
18
0
Order By: Relevance
“…As these urine data are novel we are unable to compare with any previously published data, notably the degree of individual variability. Mouritsen and colleagues have shown that serum testosterone is variable in a longitudinal study of 20 adolescents (10 male) with sample collection biannually for five years [ 28 ]. Individual hormone curves showed testosterone levels fluctuated during the study, though the overall pattern demonstrated an increase in serum hormones testosterone (as assayed by LC-MS/MS and immunoassay) from recruitment to the end of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…As these urine data are novel we are unable to compare with any previously published data, notably the degree of individual variability. Mouritsen and colleagues have shown that serum testosterone is variable in a longitudinal study of 20 adolescents (10 male) with sample collection biannually for five years [ 28 ]. Individual hormone curves showed testosterone levels fluctuated during the study, though the overall pattern demonstrated an increase in serum hormones testosterone (as assayed by LC-MS/MS and immunoassay) from recruitment to the end of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Tukey-Kramer post-hoc statistics (q=2.648; α=0.05) showed significant differences in nail testosterone levels between men and boys (difference 1.758; P<0.0001). These results support previous findings reported in the literature where testosterone concentrations are higher in men and women than in boys and girls (Andersson et al 1997;Mouritsen et al 2014). In this analysis, we found a two-fold difference between men and women's testosterone levels.…”
Section: Resultssupporting
confidence: 93%
“…Though steroid hair testing has been developing for wider use over the past decade, our literature search showed that most wildlife and domestic animal studies only measured cortisol in hair. The validation of other steroids, such as testosterone, may provide additional information on topics such as reproductive ecology (Bryan et al, 2014), social status (Koren et al, 2006), potential growth (Mouritsen et al, 2014), and social behaviours (e.g., Finkler & Terkel, 2010;Salas et al, 2016).…”
Section: Discussionmentioning
confidence: 99%